Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
ta có
a. (5x-7)(x-9)-(-x+3)(-5x+2)= 2x(x-4)-(x-1)(2x+3)
\(\Leftrightarrow5x^2-52x+63-\left(5x^2-17x+6\right)=2x^2-8x-\left(2x^2+x-3\right)\)
\(\Leftrightarrow-35x+57=-9x+3\Leftrightarrow26x=54\Leftrightarrow x=\frac{27}{13}\)
b. (x-3)(-x+10)+(x-8)(x+3)= (5x^2-1)(x+3)-5x^3-15x^2
\(\Leftrightarrow-x^2+13x-30+x^2-5x-24=5x^3+15x^2-x-3-5x^3-15x^2\)
\(\Leftrightarrow8x-54=-x-3\Leftrightarrow9x=51\Leftrightarrow x=\frac{17}{3}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a: \(\Leftrightarrow5x^2-45x-7x+63-\left(5x-2\right)\left(x-3\right)=2x^2-8x-2x^2-3x+2x+3\)
\(\Leftrightarrow5x^2-52x+63-\left(5x-2\right)\left(x-3\right)=-9x+3\)
\(\Leftrightarrow5x^2-52x+63-5x^2+15x+2x-6=-9x+3\)
=>-37x+57=-9x+3
=>28x=-54
hay x=-27/14
b: \(\Leftrightarrow-x^2+19x+3x-30+x^2-5x-24=\left(5x^2-1\right)\left(x+3\right)-5x^3-15x^2\)
\(\Leftrightarrow17x-54=5x^3+15x^2-x-3-5x^3-15x^2\)
=>18x=51
hay x=17/6
![](https://rs.olm.vn/images/avt/0.png?1311)
a)
<=> 10x - 35 + 16x - 10 = 5
<=> 10x + 16x = 5 + 35 + 10
<=> 26x = 50
<=> x = 50/26 = 25/13
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 2x^2 + 3( x-1)(x+1) - 5x(x+1)
= 2x^2 + 3( x^2 -1 ) - 5x(x+1)
= 2x^2 + 3x^2 - 3 - 5x^2 - 5x
= -5x -3
![](https://rs.olm.vn/images/avt/0.png?1311)
a. \(5x\left(2x-7\right)+2x\left(8-5x\right)=5\)
\(\Rightarrow10x^2-35x+16x-10x^2=5\)
\(\Rightarrow-19x=5\)
\(\Rightarrow x=-\frac{5}{19}\)
b. \(x\left(x-\frac{1}{3}\right)-\frac{1}{2}x\left(2x-3\right)=\frac{1}{4}\)
\(\Rightarrow x^2-\frac{1}{3}x-x^2+\frac{3}{2}x=\frac{1}{4}\)
\(\Rightarrow\frac{7}{6}x=\frac{1}{4}\)
\(\Rightarrow x=\frac{3}{14}\)
c. \(5\left(x^2-3x+1\right)+x\left(1-5x\right)=x-2\)
\(\Rightarrow5x^2-15x+5+x-5x^2=x-2\)
\(\Rightarrow-14x+5=x-2\)
\(\Rightarrow-14x-x=-2-5\)
\(\Rightarrow-15x=-7\)
\(\Rightarrow x=\frac{7}{15}\)
a, \(5x\left(2x-7\right)+2x\left(8-5x\right)=5\)
\(\Leftrightarrow10x^2-35x+16x-10x^2=5\)
\(\Leftrightarrow-19x=5\Leftrightarrow x=-\frac{5}{19}\)
b, \(x\left(x-\frac{1}{3}\right)-\frac{1}{2}x\left(2x-3\right)=\frac{1}{4}\)
\(\Leftrightarrow x^2-\frac{1}{3}x-x^2+\frac{3}{2}x=\frac{1}{4}\)
\(\Leftrightarrow\frac{7}{6}x=\frac{1}{4}\Leftrightarrow x=\frac{3}{14}\)
c, \(5\left(x^2-3x+1\right)+x\left(1-5x\right)=x-2\)
\(\Leftrightarrow5x^2-15x+5+x-5x^2=x-2\)
\(\Leftrightarrow-15x+7=0\Leftrightarrow x=\frac{7}{15}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a. (3x - 1).(2x + 7) - (x + 1).(6x - 5) = 16
<=> 6x^2 + 19x - 7 - (6x^2 + x - 5) = 16
<=> 18x - 2 = 16
<=> 18x = 18
<=> x = 1
b. (10x + 9).x - (5x - 1).(2x + 3) = 8
<=> 10x^2 + 9x - (10x^2 + 13x - 3) = 8
<=> -4x + 3 = 8
<=> -4x = 5
<=> x = -5/4
c. (3x - 5).(7 - 5x) + (5x + 2).(3x - 2) - 2 = 0
<=> -15x^2 + 46x - 35 + 15x^2 - 4x - 4 - 2 = 0
<=> 42x - 41 = 0
<=> x = 41/42
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(2x^2+3\left(x-1\right)\left(x+1\right)=5x\left(5-1\right)\)
\(\Leftrightarrow2x^2+3\left(x-1\right)\left(x+1\right)-5x\left(5-1\right)=0\)
\(\Leftrightarrow2x^2+3\left(x^2-1\right)-5x.4=0\)
\(\Leftrightarrow2x^2+3x^2-3-20x=0\)
\(\Leftrightarrow5x^2-20x-3=0\)
\(\Leftrightarrow x=4,144761059\)
a) \(x\left(x-2\right)-5x\left(1-x\right)-8\left(x^2-3\right)\)
\(=x^2-2x-5x+5x^2-8x^2+24\)
\(=-2x^2-7x+24\)
b) \(x\left(2x^2-3\right)-x^2\left(5x+1\right)+x^2\)
\(=2x^3-3x-5x^3-x^2+x^2\)
\(=-3x^3-3x\)